2017
DOI: 10.33425/2639-9474.1045
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge, Attitude and Practices on Fall Prevention in King Abdul Aziz Hospital, Kingdom of Saudi Arabia

Abstract: Introduction: Fall is the major public health problem, and it is the second leading cause of death due to unintentionally injury. About 424,000 fall happen every year and 250,000 fall are from the hospital. It is estimated that 30% of falls in hospitals are result in severe injury. Increased awareness and availability of fall prevention (FP) services might help to reduce the adverse effects of falls. The aim of this study was to evaluate the Knowledge, Attitude and Practices (KAP) on FP among nurses at King Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 9 publications
4
15
1
Order By: Relevance
“…Our results are consistent with the findings reported by Ganabathi and Mariappan, who found similar practices in the western region of the Kingdom of Saudi Arabia [13]. However, inconsistency prevails from other studies that demonstrated poor practices.…”
Section: Nurses' Practices Toward Fall Preventionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with the findings reported by Ganabathi and Mariappan, who found similar practices in the western region of the Kingdom of Saudi Arabia [13]. However, inconsistency prevails from other studies that demonstrated poor practices.…”
Section: Nurses' Practices Toward Fall Preventionsupporting
confidence: 91%
“…Fatal and non-fatal injuries increase after a fall incident. Although 70% of falls result in minor and non-fatal injuries, deaths caused by fall incidents among senior people are still a major concern [13]. In countries like the United States, 9.9 million fall-related injuries occur each year, of which 32% are older adults with a higher mortality rate of 40% [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also recommended that pаtients аt high risk of fаll should be under the cаre of experienced nurse who hаve upgrаded skills in fаll prevention. The results of a study by Ganabathi, et al, regarding "Nurses' knowledge, attitude and practices on fall prevention in King Abdul Aziz Hospital, Kingdom of Saudi Arabia" support this conclusion, demonstrating that the majority of the nurses in the study have good practices, with a small percentage having poor practices [33]. On other hand, this finding disagreed with study by Negаsh, who conducted study entitled "Assessment of selfreported practice of nurses towards fall prevention and its associated factors in an Ethiopian hospital" When it comes to fall prevention measures overall for older female patients, less than two thirds of the nurses under study performed poorly [34].…”
Section: Discussionmentioning
confidence: 83%
“…An estimated 684,000 fatal falls occur each year, while approximately 37.3 million are serious enough to require medical attention (WHO, 2021). This can lead to an increased economic burden from medical costs and the need for social care (Ganabathi, Mariappan & Mustafa, 2017;Najafpour et al, 2019). In addition, the major public health concern is that 4% of fall-related injuries result in serious patient outcomes, such as excessive bleeding, subdural hematoma, and death (WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%